2020
DOI: 10.1002/nop2.548
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of care provision in long‐term home nursing arrangements: A triangulation of three perspectives

Abstract: Background A growing proportion of older people in Germany receive long‐term care from informal and professional caregivers at home. Their personal assessment of the individual care situation is scarcely considered. Aim This study aimed to explore the subjective views of care recipients, informal and professional caregivers on the adequacy of care provision in long‐term home care arrangements. Design and Methods Qualitative semi‐structured fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…On the other hand, caregivers may underestimate the PlwD abilities because their care focuses less on supporting the independence of the PlwD and is rather based on completing care tasks as efficiently as possible 18 . In a qualitative study about the adequacy of long‐term care provision, care recipients reported a feeling of overprotection and overprovision by their informal caregivers, assuming they do not fully understand what PlwD can do on their own 39 . The different response behavior may also be caused by differences in the interpretation of the EQ‐5D‐5L's dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, caregivers may underestimate the PlwD abilities because their care focuses less on supporting the independence of the PlwD and is rather based on completing care tasks as efficiently as possible 18 . In a qualitative study about the adequacy of long‐term care provision, care recipients reported a feeling of overprotection and overprovision by their informal caregivers, assuming they do not fully understand what PlwD can do on their own 39 . The different response behavior may also be caused by differences in the interpretation of the EQ‐5D‐5L's dimensions.…”
Section: Discussionmentioning
confidence: 99%
“… 18 In a qualitative study about the adequacy of long‐term care provision, care recipients reported a feeling of overprotection and overprovision by their informal caregivers, assuming they do not fully understand what PlwD can do on their own. 39 The different response behavior may also be caused by differences in the interpretation of the EQ‐5D‐5L's dimensions. Lay et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, NAs not knowing the older person became an obstacle to a meaningful daily life. An additional obstacle was the NAs lacking time to talk or create a relationship, which is found in the other studies within the project [11, 21, 22, 24–26] as well as in others, where lack of time entails insufficient care [41]. However, discussing lack of time can often create a defence or continue a tradition and culture about lack of time.…”
Section: Discussionmentioning
confidence: 99%
“…As the world population is growing older, the number of older persons in need of care is ever increasing, expecting to cross the threshold of 16% of the world population by 2050 (United Nations Department of Economic and Social Affairs, 2022). At the same time, professionals who are willing to do caregiving work are becoming increasingly scarce (Santos & Miguel, 2020;Seidlein et al, 2020) and informal caregivers become overburdened and distressed (Syse et al, 2022). To remedy the growing imbalance between older persons in need of care and available care, research is turning towards new technologies.…”
Section: Introductionmentioning
confidence: 99%